2016
DOI: 10.5380/avs.v21i2.47849
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO DO POTENCIAL TÓXICO REPRODUTIVO DO EXTRATO DO FRUTO DE Buchenavia sp EM RATOS MACHOS IMPÚBERES DA LINHAGEM WISTAR

Abstract: O objetivo deste trabalho foi avaliar os possíveis efeitos tóxicos do extrato aquoso do fruto de Buchenavia sp. sobre o sistema  reprodutivo de ratos impúberes, pesquisando as atividades androgênica e antiandrogênica e sinais de toxicidade sistêmica. Foi empregado o protocolo de curta duração (Teste de Hershberger)., Foram utilizados 64 ratos impúberes, divididos em oito grupos de oito animais: controle positivo, controle negativo, extrato 250mg/100g, extrato 500mg/100g, extrato 1000mg/100g,  extrato 250mg/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Nunes et al (2010) observed mild toxicity, such as increased feed and weight gain in broodings of rats fed a 10% diet of B. tomentosa fruits. On another study, the fruits aqueous extract showed no androgenic or antiandrogenic activities, nor were observed degenerative, inflammatory alterations and did not trigger systemic toxicity on the animals (Ferreira et al, 2016).…”
Section: Practical Applicationmentioning
confidence: 90%
See 1 more Smart Citation
“…Nunes et al (2010) observed mild toxicity, such as increased feed and weight gain in broodings of rats fed a 10% diet of B. tomentosa fruits. On another study, the fruits aqueous extract showed no androgenic or antiandrogenic activities, nor were observed degenerative, inflammatory alterations and did not trigger systemic toxicity on the animals (Ferreira et al, 2016).…”
Section: Practical Applicationmentioning
confidence: 90%
“…Ots fruits have pulpy flesh which is sweet when ripe, containing a single seed (Lorenzi, 2008). They are consumed fresh as juice or sweet, and in popular medicine they are used in the treatment of cough (Ferreira et al, 2016). On some regions they are considered toxic, since their consumption could cause digestive alterations and abortions in goats, sheep and cattle (Mello et al, 2010).…”
Section: Practical Applicationmentioning
confidence: 99%